PSYCHOLOGICAL-PEDAGOGICAL CONDITIONS OF DEVELOPMENT SPEECH OF FIRST GRADE STUDENTS BY SMALL MEANS FOLKLORE GENRES - І.А. Kravtsova; S.P. Svincova (Academy of Cognitive and Natural Sciences, 2006)
The aims of the lessons in the Ukrainian language, which are enlarging and activization of lexicon, forming and developing of the skills o f oral and written spuch, supplying of the mental development of pupils, are defined on the present stouge of the new junior school's development. The most important device of influence on a child is beauty and magnificence, power and expressiveness of native words. Children can understand the dupest colour of words through the words the beauty enters their souls.